Avaliação do impacto da saúde bucal sobre a qualidade de vida em pacientes com asma - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2017)
Considering that the world health organization (WHO) defines quality of life as subjective, multidimensional and includes both positive and negative aspects, the influence of oral health in this context is highlighted, researches has shown that the oral condition may affect QOL in patients with chronic diseases. In this way, the literature demonstrates that there is probably an association between oral health and asthma and that quality of life in this group of patients is impaired. The main objective of this study was to evaluate the impact of oral health on quality of life in patients diagnosed with asthma. The selection of patients was made at the Hospital Universitário Regional dos Campos Gerais - HURCG (Ponta Grossa - PR). It was characterized as a "Cross-Sectional Clinical Study" with two groups (1- Patients with asthma and 2- Control, patients without asthma), with 90 volunteers in each group. The OHIP-14 and SF-36 questionnaires were applied to the both groups and in the own form were obtained demographic data, educational level, number of teeth, dental habits and socioeconomic status. Statistical tests were applied according to the distribution of the data and the significance level adopted was 5%. Regarding the results we had the participation of 72 women and 18 men in each group, the mean age was approximately 49 years and the average number of teeth was 13.17 teeth for the asthma group and 12.78 for the control. The internal reliability of the questionnaires was assessed using the Cronbach alpha (α), all α had results ≥ 0.79. Our results indicate that asthmatic patients have a low impact of oral health on QoL and that patients with fewer teeth present a greater impact of oral health in the areas of physical pain and functional limitation. In addition, our results show that asthmatics have a worse overall QOL and that asthmatic women express a greater impact of oral health on QOL.
Keywords: Qualidade de vida; Impacto da saúde bucal; Asma; Quality of life; Impact of oral health; Asthma; CNPQ::CIENCIAS DA SAUDE